Penentuan Absolute Open Flow Potensial (AOFP) Dan Production Performance Prediction Berdasarkan Well Testing Data Pada Sumur Gas “DI” Lapangan “LA” - Nugroho Marsiyanto; M. Mahlil Nasution; Siti Fadillah (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
In a well that has been drilled (exploration), a hydrocarbon well testing process needs to be carried out, namely well testing. The purpose of well testing is to determine reservoir parameters and to determine the production capacity of a layer or formation. The